PREY PREFERENCE AND RECOGNITION BY Nucella lapillus (LINNAEUS,1758) (MOLLUSCA: GASTROPODA)1 - Matthews-Cascon, Helena (Arquivos de Ciências do Mar, 2017)
Prey preference and recognition by individuals from 13 populations of Nucella lapillus (Linnaeus,1758) from New England (USA) were studied to determine if individuals fed a single prey diet develop a preference for this prey, and if prey availability affects prey recognition. Individuals from all populations showed a preference for Mytilus edulis over Littorina obtusata in laboratory experiments, including those that prey just on L.obtusata in the field. Individuals from one other population were not able to recognize L. obtusata as prey. N. lapillus kept in a diet of M. edulis in the laboratory had its preference for this prey reinforced, but those kept in a diet of L. obtusata, did not develop a preference for this prey.